Comprehensive chemical secretory measurement of single cells trapped in a micro-droplet array with mass spectrometry1. Issue 22 (11th March 2015) - Fujita, Hideaki; Esaki, Tsuyoshi; Masujima, Tsutomu; Hotta, Akitsu; Kim, Soo Hyeon; Noji, Hiroyuki; Watanabe, Tomonobu M.
<x xml:space="preserve">Abstract</x> By trapping individual single cells in a micro-well, molecules secreted by a single cell can be analyzed using mass spectrometry.